Protocol for the development of core set of domains of the core outcome set for patients with congenital melanocytic naevi (OCOMEN project). (2nd October 2019) - Oei, W.; Fledderus, A.C.; Korfage, I.; Eggen, C.A.M.; van der Horst, C.M.A.M.; Spuls, P.I.; Brinkmann, S.J.H.; Wolkerstorfer, A.; van Kessel, M.; Pasmans, S.
Abstract: Background: Having large congenital melanocytic naevi (CMN) is associated with a psychosocial burden on patients and their parents because of its remarkable appearance and the extra care it may require. Large CMN also pose an increased risk of malignant melanoma or neurocutaneous melanosis. There is a lack of international consensus on what important outcome domains to measure in relation to treatment. This makes it difficult to compare options, to properly inform patients and their parents, and to set up treatment policy for CMN. Therefore, we aim to develop a core outcome set (COS), i.e. the minimum set of outcomes that are recommended to be measured and reported in all clinical trials of a specific health condition. This COS can be used in the follow‐up of CMN patients with or without treatment, in clinical research and practice. Methods: In the Outcomes for Congenital Melanocytic Nevi (OCOMEN) projects, we follow the recommendations from the Core Outcome Measures in Effectiveness Trials (COMET) initiative and the Cochrane Skin Core Outcomes Set Initiative (CS‐COUSIN). This project entails the following: (i) a systematic review to identify the previous reported outcomes in literature; (ii) focus groups with national and international patients and parents to identify patient‐important outcomes; (iii) classification of outcomes into outcome domains; (iv) e‐Delphi surveys in which stakeholders (patients/parents and professionals) can rate the importance of domains and outcomes; and (v) an online consensus meeting to finalize the core outcome domains of the COS. Results: The results will be disseminated by means of publication in a leading journal and presentations in international meetings or conferences. We engage international experts in CMN, both patients and professionals, to ensure the international utility and applicability of the COS.